Performance-Based Financing as a Health System Reform : Mapping the Key Dimensions for Monitoring and Evaluation - Witter, Sophie; Toonen, Jurrien; Meessen, Bruno; Kagubare, Jean; Fritsche, György; Vaughan, Kelsey (BioMed Central, 2015)
Performance-based financing is increasingly being applied in a variety of contexts, with the expectation that it can improve the performance of health systems. However, while there is a growing literature on implementation issues and effects on outputs, there has been relatively little focus on interactions between PBF and health systems and how these should be studied. This paper aims to contribute to filling that gap by developing a framework for assessing the interactions between PBF and health systems, focusing on low and middle income countries. In doing so, it elaborates a general framework for monitoring and evaluating health system reforms in general.